Livestock development planning in Uganda: Identification of areas of opportunity and challenge - Benson, Todd; Mugarura, Samuel (International Food Policy Research Institute, 2010)
Livestock are an important element of the livelihoods of many Ugandan households, and considerable efforts at economic development by the government of Uganda have focused on the livestock sector. However, these development efforts have suffered due to a lack of detailed data on the distribution of livestock in Uganda to guide the targeting of such programs. In this paper we use data from the 2008 National Livestock Census to develop a better understanding of where in Uganda there might be potential for significant investment to intensify the production of livestock and, conversely, where there are important challenges, such as conflicts between human populations and livestock that need to be addressed. This analysis is done by developing a quantitative model to predict mean livestock stocking rates at sub-county level (n = 929) that uses population density, agroecological factors, and market access as explanatory variables. A mapping of the model residuals approach is then used to identify areas in Uganda that are relatively understocked and those that are potentially overstocked. This information is then used to suggest approaches to livestock development in both types of areas.